(untitled) (Bangladesh Journal of Botany, 2023)
The germination of freshly harvested, dry-stored and wet-stored Hydrocharis dubia seeds were treated with exogenous GA3, cold stratification, puncture, different temperatures and combined treatments under controlled laboratory conditions. The results showed that: The optimal temperature for H. dubia seed germination is 23℃ and fresh seed has conditional dormancy, which can be released by puncture. Seed germination percentage decreased significantly after dry seed storage and the main reason for the reduction of "seed germination ability" by dry storage was that dry storage. caused secondary dormancy but a reduction of seed vigor. The secondary dormancy is non- deep physiological dormancy, which can be released by cold stratification, seed puncture and combination treatments. The findings provided further insight into how germination strategy contributes to the seed bank formation and species reproduction. Bangladesh J. Bot. 52(2): 429-435, 2023 (June)